Scontrone (central Italy), signs of a 9‐million‐year‐old tragedy. (23rd December 2014) - Mazza, Paul P. A.
<x xml:space="preserve">Abstract</x> The fossilierous bonebeds of Scontrone (Abruzzo region, central Italy) are preserved in tidal‐flat aeolian calcarenites at the base of the Lithothamnion Limestone, a Miocene carbonate ramp widespread in the central‐southern Apennines. The site bears evidence of a catastrophic event at 9 Ma. Reported are the results of the palaeobiological and taphonomic analysis conducted on the rich vertebrate assemblage, particularly on the remains of Hoplitomeryx (Mammalia, Artiodactyla, Ruminantia), recovered from the so‐called Scontrone calcarenites between 1992 and 2012. This is the first taphonomic study of a Late Miocene continental bone assemblage preserved in coastal deposits. The bones are not in primary context. They were likely exhumed during the initial phase of a marine transgression after a period of primary 'storage' within a possibly flood‐generated deposit in an estuarine environment. The mortality patterns indicate that the carcasses accumulated in a short time (within a year). The bones of the disarticulated skeletons were then removed, broken in a dry and brittle state, scattered over wide carbonate ramps along an arid to semi‐arid, wind‐exposed coastline and eventually buried again in aeolian calcarenites that drape transgressive tidal‐flat creek deposits. The analysis also reveals that hoplitomerycids were possibly seasonal reproducers and that the land they inhabited, the so‐called Apulia Platform, was probably swept by sudden, disastrous, storm‐supplied flash floods.